Motivasi Belajar Siswa dalam Pembelajaran Fisika - Dina Selvia (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The purpose of this study was to describe the motivation to learn physics in class X MIA at SMAN 9 Jambi City. This type of research is descriptive research with a quantitative approach. The population of this study were students of class X MIA at SMAN 9 Jambi City. The sampling technique in this research is total sampling. The research instrument used was a questionnaire on students' motivation to learn physics. The data analysis technique used is quantitative analysis using descriptive statistics. The results of this study indicate that the motivation to learn physics in class X MIA at SMAN 9 Jambi City on the intrinsic motivation dimension is in the high category with a percentage of 59,80% where students' attitudes are in the frequent category and the extrinsic motivation dimension is in the high category with a percentage of 61,76% where students' attitudes are in the frequent category. Conclusions, that the attitudes of respondents on the intrinsic motivation dimension include indicators of high learning activities tend to be in the occasional category, indicators of perseverance in doing assignments tend to be in the frequent category, and tenacious indicators in facing difficulties tend to be are in the frequent category. In the extrinsic motivation dimension, indicators of the presence of information from teachers tend to be in the always category, indicators of feedback tend to be in the frequent category, and indicators of reinforcement tend to be in the frequent category. Keywords: Learning Motivation, Physics, Intrinsic and Extrinsic Method